Regulation and privilege in transplantation tolerance. - Waldmann, H; Adams, E; Fairchild, P; Cobbold, S (Springer, 2008)
Background There are now many ways of achieving transplantation tolerance in rodents that do not require stem cell chimerism. The best studied of these utilize short courses of antibody treatment aimed at blocking the coreceptors CD4 and CD8, and/or co-stimulatory molecules such as CD40L. Unlike tolerance through mixed chimerism which can be absolute, this form of tolerance is operational with potential effector cells remaining, but under the control of CD4 regulatory T cells (Treg). Both natural and induced CD4+ CD25+ FoxP3+ Treg are involved, although other categories of Treg may also participate. Tolerated grafts can be shown to contain Treg cells, and we have proposed that they function within the graft and draining lymphoid tissue to generate a state of acquired privilege. Discussion The finding oflinked suppression in tolerance suggests that Treg are drawn into microenvironments where they decommission antigen-presenting cells, and consequently perpetuate more regulation through conversion of naive T cells to regulators. Persistent antigen from accepted transplants operating within such inhibitory microenvironments provides the basis for infectious tolerance through the life of the recipient. Regulation may operate at any stage of the rejection response. Induction of tolerance appears to involve a role for the cytokine TGFβ. This may operate both to convert naive T cells to Treg function while also subverting effector functions necessary for rejection